Effect of cotton fruiting bodies on the growth and development of spotted bollworm Earias vittella - Shera, P S; Arora, Ramesh (Indian Journal of Plant Protection, 2020)
Growth and development parameters of spotted bollworm, Earias vittella (Fabricius) were compared on two cotton fruiting bodies (squares and bolls) at the Entomological Research Farm, Department of Entomology, Punjab Agricultural University, Ludhiana during 2011. The larvae when fed on squares and bolls showed significant differences for all parameters studied, viz., survival, duration, morphometry and nutritional indices. Larval survival and duration were significantly lower on squares (64.7 to 67.3 %; 8-13 days) as compared to bolls (68.7 to 72.0 %; 10-15 days). Similar observations were recorded for pupal survival and pupal period, being significantly lower on squares (85.6 to 91.1%; 7-18 days) as against bolls (89.3 to 100 %; 7-21 days). The survival index was also less in case of larvae that were fed on squares (0.56 to 0.61) as compared to those fed on bolls (0.61 to 0.72). Both larval and pupal period of E. vittella increased with subsequent months, being shortest in August followed by September and October-November months. Pupal (length, breadth and weight) and adult (body length and wing expanse) measurements were significantly less when larvae were fed on squares as compared to bolls. The cotton fruiting bodies significantly affected all nutritional indices for larval food consumption and utilization, viz., consumption index (CI), relative growth rate (RGR), approximate digestibility (AD), efficiency of conversion of digested food (ECD) and efficiency of conversion of ingested food (ECI); the figures were lower for larvae fed on cotton squares than for larvae that fed on cotton bolls. These findings further our understanding that how E. vittella development, morphometry and nutritional indices are affected by cotton fruiting bodies as food source. The present findings could be useful in devising an effective integrated pest management strategy against spotted bollworm on cotton crop.